Diagnóstico de la gestión de los residuos sólidos urbanos en el cantón Guano - Agila Jiménez, Diego Alexander (2024)
The development of society, marked by technological advancements, industrial expansion, commercial activities, and population growth, has led to a significant increase in the generation of solid waste. This surge poses a formidable challenge for developing countries, primarily due to the absence of comprehensive, long-term strategies for solid waste management and a dearth of transparent information regarding urban solid waste. This research aims to conduct a comprehensive diagnosis of urban solid waste management in the Guano canton. Initially, a meticulous analysis of both primary and secondary data was undertaken to delineate the various phases of solid waste management in the canton. The quartering method was subsequently employed to ascertain the physical composition of Municipal Solid Waste (MSW), enabling the determination of per capita generation, density, and volume of waste in Guano City. Additionally, through field visits, the study investigated the MSW collection model operational in Guano, along with the present status of emergent cells designated for MSW disposal. Urban solid waste collection in the Guano canton occurs six days a week, following a curbside collection model that covers 86% of the area. The per capita generation stands at 0.926 kg/person/day, with a density of 231.86 kg/m3. The physical composition analysis reveals that organic waste accounts for 54.86%, plastics for 16%, and rejects for 12% of urban solid waste. The designated waste disposal area is situated 6.50 km away from the urban core, albeit it faces certain limitations, notably the lack of daily solid waste coverage.